Angiotensin II Regulates Islet Microcirculation and Insulin Secretion in Mice. (February 2014) - Ihoriya, Chieko; Satoh, Minoru; Kuwabara, Atsunori; Sasaki, Tamaki; Kashihara, Naoki
Abstract Objective Angiotensin II causes potent increases in systemic and local pressure through its vasoconstrictive effect. Despite the importance of angiotensin II for local blood flow regulation, whether angiotensin II regulates the pancreatic islet microcirculation remains incompletely understood. We hypothesized that angiotensin II directly regulates the pancreatic islet microcirculation and thereby regulates insulin secretion. The aims of this study were to develop a new technique to visualize pancreatic islet hemodynamic changes in vivo and to analyze changes in islet circulation induced by angiotensin II or an angiotensin type 1 receptor blocker. Methods Using an in vivo imaging method, we observed the pancreatic islet microcirculation. Various doses of angiotensin II or an angiotensin type 1 receptor blocker were injected intravenously, and changes in islet microcirculation were observed. Glucose‐stimulated insulin secretion from the pancreas was measured from the hepatic portal vein. Results We identified islet microcirculation using a fluorescent dye. Angiotensin II significantly induced blood vessel contraction in the islets in a dose‐dependent manner. In contrast, the angiotensin type 1 receptor blocker induced vasodilation. Glucose‐stimulated insulin secretion was decreased by angiotensin II infusion. Conclusions These results show that angiotensin II is involved in the regulation of pancreatic islet microcirculation and insulin secretion.